The social pillar of sustainability: a quantitative approach at the farm level - Anna Gaviglio; Mattia Bertocchi; Maria Elena Marescotti; Eugenio Demartini; Alberto Pirani (Agricultural and Food Economics, 2016)
The present research proposes a model for the assessment of the social pillar of sustainability at the farm scale. Contrary to what is available for the environmental and economic pillars, there is a considerable lack of exhaustive approaches able to evaluate the social dimension of sustainability in rural areas. Thus, the idea was to create a mean by which a quantitative evaluation of the social characteristics of farms could be made. The study involved farms of the South Milan Agricultural Park, located in northern Italy. Thirty sampled farms were selected in order to represent the different livestock systems, land areas, economic dimensions and levels of multifunctionality of the area. The framework is based on a set of 15 indicators able to evaluate five main social "components": (i) quality of the products and the region, (ii) short supply chain and related activities, (iii) work, (iv) ethical and human development and (v) society, culture and ecology. The work was structured using the following steps: identification of the relevant variables for the social sustainability of farms, determination of the framework of indicators, assignment of their range scores, data collection, calculation of the score for each farm, data analysis and visualization. The method allows different types of analysis in relation to the objective of the research. Three main approaches were individuated: (1) the comparison among farms is the "farms' ranking" and the "aggregate ranking"; (2) the evaluation of single themes of sustainability is the "single indicator evaluation" approach and (3) the temporal comparison of the farm's result is the "score evolution" approach. The method showed a high sensitivity to the multifunctionality and the type of farm production, especially organic vs conventional, while other characteristics, such as the type of livestock and the land area, seem to differentiate the sample less or to characterize it in only a few social components. The work has underlined the importance and the advancement in the study of the social dimension that, however, needs further in-depth analysis through comparison with the other two pillars and among various social states in different rural areas.
Keywords: 330; Social sustainability; Agricultural sustainability; Indicators; Farm performance; Multi-attribute analysis